2020
DOI: 10.3390/antiox9090819
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins: From the Field to the Antioxidants in the Body

Abstract: Anthocyanins are biologically active water-soluble plant pigments that are responsible for blue, purple, and red colors in various plant parts—especially in fruits and blooms. Anthocyanins have attracted attention as natural food colorants to be used in yogurts, juices, marmalades, and bakery products. Numerous studies have also indicated the beneficial health effects of anthocyanins and their metabolites on human or animal organisms, including free-radical scavenging and antioxidant activity. Thus, our aim wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 129 publications
0
49
0
Order By: Relevance
“…As mentioned before, the neuroprotective effects showed by anthocyanins are mainly due to their ability to cross the blood–brain barrier and protect neurons and glia cells from oxidative damage induced by reactive species and free radicals, reduce the inflammatory cytokines and β -amyloid concentrations, and to suppress NF- k B, the Nf E2-related factor-2 (Nrf-2) signalling pathway, COX, and caspase activities [ 119 ]. Furthermore, anthocyanins also can raise gene expression, GTPase activity, and detoxifying enzyme amounts, and therefore meliorate cerebrovascular and peripheral blood flow [ 196 ].…”
Section: Putative Health Benefitsmentioning
confidence: 99%
“…As mentioned before, the neuroprotective effects showed by anthocyanins are mainly due to their ability to cross the blood–brain barrier and protect neurons and glia cells from oxidative damage induced by reactive species and free radicals, reduce the inflammatory cytokines and β -amyloid concentrations, and to suppress NF- k B, the Nf E2-related factor-2 (Nrf-2) signalling pathway, COX, and caspase activities [ 119 ]. Furthermore, anthocyanins also can raise gene expression, GTPase activity, and detoxifying enzyme amounts, and therefore meliorate cerebrovascular and peripheral blood flow [ 196 ].…”
Section: Putative Health Benefitsmentioning
confidence: 99%
“…Black rice ( Oryza sativa L.) and purple corn ( Zea mays L.) have been described as novel sources of natural antioxidants. They are rich in anthocyanins and phenolic compounds [ 21 , 22 ], which play a role as antioxidant that their structure can be able to donate electrons to the free radicals with unpaired electrons and reduce agents in the electron-transfer reaction pathway [ 23 ]. Antioxidant activity of anthocyanin also increased desaturase enzymes activity for converting monounsaturated fatty acid (MUFA) to polyunsaturated fatty acid (PUFA) or inserting additional unsaturated bonds into already existing PUFA [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several health benefits have been ascribed to anthocyanins, not only related to their antioxidant activities. In vivo studies on humans and model animals have reported potential anti-diabetic, anti-inflammatory and cardioprotective activities, along with hepato- and nephroprotection, and anti-atherogenic activities, among others [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%